Penerapan Model High Scope dalam Pembelajaran Matematika Permulaan Anak Usia Dini - Maulidya Ulfah; Monika Nurlaela; Saifuddin Saifuddin (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2022)
The skills needed by children to understand mathematics are the ability to identify mathematical concepts that children can learn through play activities. Basically, children need meaningful activities, children like to take part in the activities of adults so that they feel useful and feel needed. This study aims to determine the learning process by using high scope models in learning mathematics beginning of early childhood at TKIT Sabilul Huda. The high scope model is a learning model based on the development of interactions. This learning model emphasizes the importance of direct child involvement and this learning model is child-centered. The methods and media used by the teacher in terms of learning mathematics beginning for children are less interesting and very far from the word fun for children. This study uses a descriptive qualitative research method, with a focus on research on the application of the high scope model in early childhood mathematics learning, while the primary data sources are principals, center class teachers, and children. The secondary data sources are references to both books and journals related to high scope models and mathematics beginning of early childhood. Data collection techniques using observation, interview, and documentation techniques. And checking the validity of the data using triangulation. The results of the study showed that the application of high scope models in mathematics learning for early childhood at the TKIT Sabilul Huda had been done well from the planning of learning, implementation, and evaluation of learning. The results of the application of the high scope model in early childhood mathematics learning can be seen from the teacher's assessment, the performance of the child and the work of the child who gets the value of developing very well and developing as expected.